Negotiating Tradition and Technology: Refiguration of Arab-Malay Nazhom in Technology-Based Fiqh Safinah Learning at SMK Kesehatan NW Teros, East Lombok - Fathurrahman; Muslich (Lembaga Bale Literasi, 2026)
This study examines the negotiation process between Arab-Malay nazhom-based Islamic scholarship traditions and the utilisation of information technology in Fiqh Safinah learning at SMK Kesehatan NW Teros, East Lombok. This transformation is understood as a pedagogical refiguration effort that not only preserves traditional values but also adapts them to a more contextual digital ecosystem suited to contemporary learners. An explanatory survey design was employed, measuring the influence of technology-based media on students' levels of comprehension, motivation, and engagement in fiqh learning. Data were collected through structured questionnaires administered to 30 students and analysed using descriptive and inferential statistical techniques. Results indicate that integrating Arab-Malay nazhom into digital platforms significantly contributes to improvements in students' conceptual and affective understanding of Fiqh Safinah material. Furthermore, information technology proved capable of enhancing the appeal of learning without displacing the substantive tradition of Islamic scholarship. Simple regression analysis yielded a coefficient (? = 0.68, p < 0.001), confirming a statistically significant and strong effect of technology use on learning outcomes. These findings affirm that the negotiation between tradition and technology is not a contradictory relationship but is dialectical and productive in constructing an adaptive and sustainable fiqh learning model.